Low Power Quantum-cascade Laser Photoacoustic Spectrometer for Trace-gas Monitoring - Nägele, Markus; Hofstetter, Daniel; Faist, Jérôme; Sigrist, Markus W. (My University, 2001)
The development of a novel type of highly sensitive multipass resonant PA cell for trace-gas detection enables the use of new compact low-power laser sources such as quantum-cascade lasers (QCLs) because the effective power present in the cell is increased by a factor of ~ 20 compared to a one-pass arrangement. Based on an existent mobile CO2 -laser photoacoustic (PA) spectrometer we implemented additionally a pulsed QCL with a tunable emission wavelength between 981.5 cm-1 and 983.5 cm-1 working near room temperature as pump source. Its average power is ≤ 1.7 mW and the laser-line width is < 0.2 cm-1. With reference to HITRAN data a minimum measurable absorption coefficient αmin = 2.2×10-5cm-1 corresponding to a minimum measurable line intensity Smin = 2.5×10-25 cm-1/(molecule⋅cm-2) is achieved even at the low QCL power. First measurements are presented to characterize the performance of our QCL based system.